Digitization Of Msmes, Economic Challenges Of Bonto Bulaeng Village, Sinoa District In The Era Of Society 5.0 - Agunawan, Agunawan; Ifani, Aulyah Zakilah; Jama, Ilham Muhadir (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
Digitalization in the Society 5.0 era is a comprehensive transformation process that integrates digital technology into all aspects of human and societal life. It is not only about turning analog information into digital, but also about using digital data and technology to create new value, optimize processes, and improve the quality of life. Bonto Bulaeng Village has potential in dragon fruit plantations, diversification of agricultural products, and local handicrafts. However, MSME actors in this village still face challenges related to business management, marketing, and wider market access. This service aims to assist MSME actors in Bonto Bulaeng Village in improving entrepreneurial knowledge and skills, optimizing the use of digital technology for marketing, encouraging product diversification, increasing understanding of product packaging, and increasing the adaptive capacity of MSMEs to market changes. This is done through various interventions, such as training, mentoring, and socialization. It is hoped that with this service, MSMEs in Bonto Bulaeng Village can increase competitiveness, diversify products, and use digital technology for marketing, so that they can increase people's income and welfare.